Effect of Corn Type and Form of Supplement on Grazing Steers – Year 2 - Jaymelynn K. Farney; Harley Allen; Larissa Muniz (Kansas Agricultural Experiment Station Research Reports, 2023)
Eighty stocker steers were grazed on bromegrass from the end of May to the middle of August and were provided five different feeds while on grass during the summer. Treatments evaluated included (1) mineral only; (2) free-choice supplementation in the form of liquid feed (MIX30) or (3) block format (Mintrate 40 Red); and hand-fed supplements of 60% corn:40% dried distillers grains at 0.5% of body weight on a dry matter basis offered daily where the corn was either an (4) isoline corn (ISO; parent genetic line) or (5) Enogen feed corn (ENO; includes alpha-amylase gene). Steers were weighed every 28 days while on grass and were measured for carcass quality by ultrasound prior to being sold. Hand-fed steers had greater gain than self-fed supplemented steers and these steers tended to have more backfat, marbling, and did have more muscle depth coming off grass than other supplemented steers. Steers that received free-choice mineral or self-fed supplements also had lower gains than steers being hand-fed supplement. During a drought year overall, supplemented steers had a greater gain than non-supplemented controls (receiving mineral only). This advantage became apparent after 56 days on grass when the drought was the most severe and the difference may have become more pronounced if the steers hadn’t been removed from the pasture due to limited biomass. Overall, hand-feeding is the method that maintained a more consistent gain, regardless of pasture quality and biomass production. Evaluation of operational costs of production need to be evaluated before determining if the hand-feeding management strategy is the best for returns to the operation.
Keywords: amylase corn; protein block; liquid feed; hand-fed; steers